The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.35940/ijitee.b7730.129219
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cloud Computing In Higher Education of Pakistan

Kashif Ishaq*,
Adnan Abid,
Shoaib Farooq
et al.

Abstract: Cloud computing is an internet-based service of delivering technology to users and an important technological facility where mutual resources are delivered on demand. Usage of cloud computing in educational Institutions provides students as well as administrative staff an opportunity to access various applications and knowledge swiftly. Its simplicity, upfront-cost, reduced downtime and less management effort make this service acceptable for all fragments of society particularly students and teachers. Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In depth, N-gram models were applied with and without stemming categories. Further, the outcomes showed that SVM classifier utilizing TFIDF with stemming inside bigrams features highlight bettered the situation execution [57].…”
Section: Discussionmentioning
confidence: 96%
“…In depth, N-gram models were applied with and without stemming categories. Further, the outcomes showed that SVM classifier utilizing TFIDF with stemming inside bigrams features highlight bettered the situation execution [57].…”
Section: Discussionmentioning
confidence: 96%
“…The paradigm of all domains of life has been rapidly shifting from physical to online means [1]. Education has also been revolutionized with the improvement in technology [2], [3]. Education includes not only learning but also assessment of learning that raise questions about credibility of traditional methods of assessment [4].…”
Section: Introductionmentioning
confidence: 99%